PENGGUNAAN METODE ANTROPOMETRI PADA SISTEM INFORMASI MONITORING PERKEMBANGAN STATUS GIZI (SIMOPSGI) BALITA (Studi Kasus: Posyandu Melati Pasar Kemis Kabupaten Tangerang) - Aisyah Farisa Jasmine (2020)
Nutritional problems in Indonesia is a serious problem to solved. Moreover in toddler, cases of malnutrition are still a challenge in the formation of future generations. One of the government's efforts to improve health problems is to establish a Posyandu (Integrated Service Post), which is specifically for children aged 0 - 5 years. In Posyandu, the measurement carried out by the Anthropometry method. However, at this time Posyandu has not been too instrumental in helping to solve nutrition problems, because there is no system that can monitor the nutritional status. The Posyandu data management process is still manual, and parents have limited information about providing proper nutrition for children. In effort to improve Posyandu services, it need a system to help in monitor nutritional status, as well as the effectiveness of the performance of officers at the Posyandu by helping parents access nutritional information. The information system is made based on the web. The system development method uses the prototyping method, and built with Laravel framework. The expected outcome of this study is information system for monitoring development of the nutritional status of toodler using the Anthropometric measurement method, it expected to facilitate information delivery between users.